Public policy for meningococcal vaccination - J. Claire Cameron (Taylor & Francis Group, 2018)
On an individual basis, meningococcal disease is consistently shown to be one of the most feared potential childhood infections. On a population level, any clustering of cases or increase in disease requires proactive health protection management, while epidemics can be devastating. It is therefore no surprise that developing protective meningococcal vaccines and effective strategies for their implementation has been a continuing public health priority for some decades.